A molecular electron density theory study of the higher-order cycloaddition reactions of tropone with electron-rich ethylenes. The role of the Lewis acid catalyst in the mechanism and pseudocyclic selectivity. (6th December 2021) - Domingo, Luis R.; Pérez, Patricia
Abstract : Weak attractive/repulsive electronic interactions control the [4+2]/[8+2] pseudocyclic selectivity in Lewis acid catalyzed cycloaddition reactions of tropone with nucleophilic ethylenes. Abstract : The higher-order cycloaddition reactions of tropone with nucleophilic ethylenes, in the absence and presence of Lewis acid (LA) catalysts, have been studied within Molecular Electron Density Theory (MEDT) at the ω B97X-D/6-311G(d, p) and B3LYP-D3BJ/6-311G(d, p) computational levels. The strong electrophilic character of tropone, enhanced by the presence of LAs, allows its participation in polar cycloaddition reactions of reverse electron density flux (REDF) towards nucleophilic ethylenes. Analysis of the Parr functions indicates that the C2 and the C4 positions of tropone are the most electrophilic centers. These polar higher-order cycloaddition reactions take place via a non-concerted two-stage one-step or a two-step mechanism, yielding only one cycloadduct via a total regio and pseudocyclic selectivity. The present MEDT study allows establishing that these higher-order cycloaddition reactions are kinetically controlled by nucleophilic/electrophilic interactions taking place at the polar transition state structures (TSs). LAs not only accelerate the reaction and make it completely regioselective but also determine the pseudocyclic selectivity yielding exclusively [4+2] or [8+2] cycloadducts, which depends on a series of weak attractive/repulsive intramolecular electronic interactions present at the corresponding diastereoisomeric TSs.